Manejo ecológico de insectos chupadores en el cultivo de pepino (Cucumis sativus L.) - Morejón Díaz, Danny Marcial (2022)
This document deals with the ecological management of sucking insects in cucumber crops (Cucumis sativus L.). Cucumber is a vegetable that has achieved great importance due to the great diversity of climates and its adaptability; It is consumed fresh or industrialized, since most horticultural crops are rich in vitamins and easily digestible. The conclusions determine that cucumber cultivation has a high rate of consumption, both fresh and industrialized, representing a production alternative for the farmer, both for the domestic market and for export purposes; In Ecuador, one of the main phytosanitary problems in horticultural crops is the severe attack of insect pests of great economic importance, the whitefly, because the use of chemical insecticides causes insect resistance to these products and, in turn, the resistance of insects to these products. pollution; The best method of ecological control is the application of plant-based botanical extracts, since the plants have a composition that inhibits the proliferation of sucking insects, reducing the damage threshold in the cucumber crop and the associated systems have an effect on the population occurrence of beneficial insects since in general a trend of greater number was found in the plot in association of cucumber with another cultivar, compared to the plots of crops alone and expresses a higher yield per unit area than crops alone .